Detection of the onset of agitation in patients with dementia: real-time monitoring and the application of big-data solutions. (1st January 2013) - Moore, Philip; Thomas, Andrew; Tadros, George; Xhafa, Fatos; Barolli, Leonard
The changing demographic profile of the population has potentially challenging consequences resulting in a rapidly growing elderly population with healthcare implications including Alzheimer type conditions (a leading cause of dementia). Dementia requires long term care to manage the negative behavioural symptoms which are primarily exhibited in terms of agitation and aggression. This article considers dementia with a discussion around independent assisted living (IAL). We discuss the behavioural and psychological symptoms of dementia (BPSD) and the factors (precursors) to the onset of agitation and aggression. Context and data processing is introduced and the nature of knowledge considered. Next generation context-aware systems are considered with the focus on health monitoring. We postulate that the challenges lie in the effective realisation of IAL; achieving this however remains an objective of intensive multi-disciplinary research involving both clinicians and computer science in the development of software and non-invasive sensor technologies implemented in mobile systems.